PERSEPSI FOTOGRAFER PROFESIONAL DALAM PEMAKNAAN FOTO KONSEPTUAL KARYA DARWIS TRIADI DI BUKU “EMOSI SEBUAH FOTO” - Zufar Alrozan; Ageng Soeharno (Empat Sembilan Publisher, 2025)
This study aims to determine the perceptions of professional photographers in interpreting conceptual photographs by Darwis Triadi in the book